Constituir-se educador em ambiência humanista: protagonismo docente e desenvolvimento profissional no IFSUL - Sehn, Leandro Roberto (2022)
This thesis, called “Becoming an Educator in a Humanist Ambience: Teaching Protagonism and Professional Development at IFSUL”, was developed in the Graduate Program in Education, research line “Teaching, Knowledge and Professional Development”, at the Federal University of Santa Catarina. Maria, Rio Grande do Sul, Brazil. The main research question asks “What interinfluences do bachelor teachers play a leading role in their professional teaching development and the process of becoming an educator in the ambience of a Federal Institute of Education, Science and Technology?”. Consequently, the general objective was to understand the inter-influences between the protagonism of bachelor professors in their professional teaching development and the process of becoming an educator in the environment of the Federal Institute of Education, Science and Technology Sul-rio-grandense (IFSul - Câmpus2 Venâncio Aires). The following dialogical propositions are relevant: a) configuration of the ambience of IFSul; b) conditions of ambience and teaching protagonism; c) technical training versus humanistic training; d) self-perception of the teaching trajectory and professional development in the Institution and course. A qualitative method was used in research in education, through self-narratives in sensitive listening to bachelor professors of the faculty of the Technical Course in Computing Integrated to High School at IFSul - Campus Venâncio Aires. The research promoted dialogical and interactive moments, of [re]signification of memory and experience, valuing the individual history and its connection with the history of the Institution and its insertion in the teaching profession. From the educators' narratives, it is possible to understand that, by promoting sensitivity to the human, the ambience of the institution enhances the movements of self-discovery that germinate self-(trans)formative processes that are established in each teacher. At the same time, breaking the paradigm of personal-professional distance strengthens relationships and expands opportunities for sharing knowledge. This dynamic is reflected in professional development with the support of the institution and the support of colleagues, little by little promoting the formation of teaching that, upon discovering itself as human, starts to play a leading role as human teaching as well.